Complete Reducibility for Quasilinear Hyperbolic Systems (Journal of Partial Differential Equations, 2006)
In this paper we present a necessary and sufficient condition to guarantee the complete reducibility for quasilinear hyperbolic systems and give some examples.
Keywords: Complete reducibility; Quasilinear hyperbolic system